2008
DOI: 10.1016/j.jvs.2008.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Endovenous laser and echo-guided foam ablation in great saphenous vein reflux: one-year follow-up results

Abstract: Overall, endovenous laser ablation achieved higher occlusion rates than echo-guided chemical ablation with foam after one year follow-up. Matching the patient to the technique based on great saphenous vein diameter measured before treatment may assist in boosting the treatment success rate to >90%. A larger patient cohort followed and compared over a longer period of time would be required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 30 publications
2
42
0
1
Order By: Relevance
“…There was no difference noted in correlation tables between VCSS and VTE risk assessment score comparing VCSS for all limbs and random sampling of VCSS based on one limb per participant. Based on the modified CIVIQ assessment, overall mean score for each participant (n ϭ 2907) as per general category included: Quality of Life (QoL)-Pain 6.04 Ϯ 3.12 (range, 3-15), QoL-Functional 9.90 Ϯ 5.32 (range, , and QoL-Social 5.41 Ϯ 3.09 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15]. Overall correlation between CIVIQ and VCSS for all limbs was moderately strong (r s ϭ 0.43; P Ͻ .0001), with highest correlation noted for pain (r s ϭ 0.55; P Ͻ .0001) and edema (r s ϭ 0.30; P Ͻ .0001; Table V).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no difference noted in correlation tables between VCSS and VTE risk assessment score comparing VCSS for all limbs and random sampling of VCSS based on one limb per participant. Based on the modified CIVIQ assessment, overall mean score for each participant (n ϭ 2907) as per general category included: Quality of Life (QoL)-Pain 6.04 Ϯ 3.12 (range, 3-15), QoL-Functional 9.90 Ϯ 5.32 (range, , and QoL-Social 5.41 Ϯ 3.09 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15]. Overall correlation between CIVIQ and VCSS for all limbs was moderately strong (r s ϭ 0.43; P Ͻ .0001), with highest correlation noted for pain (r s ϭ 0.55; P Ͻ .0001) and edema (r s ϭ 0.30; P Ͻ .0001; Table V).…”
Section: Resultsmentioning
confidence: 99%
“…5,6 Despite lack of extended validation, there has been general acceptance and wide dissemination of VCSS for clinical and research purposes. [7][8][9][10][11][12][13][14] With the creation of the AVF, the National Venous Screening Program (NVSP) in 2005, and its expansion in 2007, 15,16 several standard venous assessment tools were incorporated into the screening process as independent determinants of venous disease severity, but correlation between these instruments as a global venous screening tool has not been tested. The scope of this study is to assess the validity of VCSS and its integration with other venous assessment tools as a global venous screening instrument.…”
mentioning
confidence: 99%
“…Gonzalez Zeh 29 reported 93% vs 33% obliteration rate for GSV trunk below 8mm and above 12 mm respectively after UGFS.…”
Section: Discussionmentioning
confidence: 97%
“…Rodrigo et al [8] reported on 53 patients their classification was as follow 30.2% belong to C2, 30.2% to C3, 18.9% to C4, 11.3% to C5 and 9.4% to C6. According to anatomical classification 100% were superficial and also 100% were primary GSV treated in all patients.…”
Section: Citationmentioning
confidence: 97%